Edgeless and eccentric cities or new peripheries? - Limonad Ester; Costa Heloisa (Bulletin of Geography. Socio-Economic Series, 2014)
Changes in the organisation of social space, set in motion by the third industrial revolution, affected the spatial distribution of production and population, challenging established conceptions of centralities and urban networks at different scales. Temporal continuities and simultaneities are replacing spatial ones, as urban agglomerations expand in scattered ways. Material and immaterial economic flows are followed by economic and political spatial rearrangements. Eccentric centralities outside urban agglomerations emerge as a result of these spatial movements. The concept of centre-periphery used to be essential to distinguish differences, inequalities and asymmetries in social space, but contemporary urban and metropolitan sprawl defies previous centre-periphery correlations. Our goal is to discuss the changing notion of centralities within contemporary urbanisation. Hence following a theoretical approach on centralities, poles and positioning, the spatial context of the Belo Horizonte Metropolitan Region is explored as it is experiencing an increasing spatial dispersion of economic activities, population and political power against an historical backdrop of strong centre-periphery relationships. Finally as a closure after analysing the spatial outcome of the Belo Horizonte Metropolitan Region and its perspectives, some questions are enrolled to help to understand the challenges posed to metropolitan planning, in the context of economic articulation with the more general global process and socio- environmental and political requirements usually prevailing at the local/metropolitan leve